Kecerdasan Emosional Perempuan Kuwait dalam Novel ’Uyūn ’alas-Samā‘ - Muasomah (MUWAZAH : jurnal kajian gender, 2019)
This research aims to reveal the emotional intelligence of women in Kuwait society in the novel ‟Uyūn ‟alas- Samā„ by Qumāsyah al-‟Alyān. This study uses an analysis of feminist literary criticism. The method used in this research is library research. Meanwhile, emotional intelligence in the beginning is a person's ability in motivating themselves and respond to the mood appropriately. There are five major regions in emotional intelligence, they are recognizing emotions, managing emotions, motivating oneself, recognizing emotions in others, and build relationships. A person's ability against those regions can be different from each other. The results showed that woman who is reflected in this novel has high emotional intelligence despite living in a family with Kuwaiti backgrounds who tend to be patriarchal. However, supported by emotional intelligence, the woman character in this novel is able to survive and rise from the slump she experienced. From the five major regions of emotional intelligence, the woman in the novel is able to recognize emotions properly, manage emotions, motivate oneself, recognize emotions in others, and build relationships. As for the main five regions of emotional intelligence of woman in this novel which tend to be higher is the ability to motivate her self to the problem